Malnutrition determined by the controlling nutritional status score, prognostic nutritional index and hemoglobin-albumin-lymphocyte-platelet score is associated with prolonged hospital stay in liver cancer patients who underwent interventional treatment - Zhang, Zhanshang; Liao, Lian; Zeng, Yuanbiao; Ouyang, Peng (Frontiers in Oncology, 2026)
BackgroundThe purpose of this study was to investigate the association between the nutritional status evaluated by the Controlling Nutritional Status (CONUT) score, Prognostic Nutritional Index (PNI) and hemoglobin-albumin-lymphocyte-platelet (HALP) score, and the prolonged hospital stay in liver cancer patients who underwent interventional treatment, in order to provide a reference for clinical optimization of the prognosis of liver cancer patients undergoing interventional treatment through nutritional assessment.Methods466 liver cancer patients who underwent interventional treatment were retrospectively analyzed. Medical records (age, gender, history of smoking, history of alcohol drinking, hypertension, diabetes mellitus, viral hepatitis, and laboratory test results) were collected. The threshold for prolonged hospital stay was defined based on the third quartile (75th percentile) of length of hospital stay. The relationship between CONUT, PNI, and HALP and prolonged hospital stay was analyzed.ResultsThe mean hospital stay of patients was 11.0 (8.0, 14.0) days. There were 337 (72.3%) patients without prolonged hospital stay (<14.0 days) and 129 (27.7%) patients with prolonged hospital stay (≥14.0 days). The proportion of moderate and severe grade malnutrition determined by CONUT score in patients with prolonged hospital stay was higher than patients without prolonged hospital stay (p=0.002). The levels of PNI (p=0.002) and HALP (p=0.003) in patients with prolonged hospital stay were higher than those in patients without prolonged hospital stay. Logistic regression analysis showed that CONUT moderate + severe malnutrition grade (odds ratio (OR): 1.634, 95% confidence interval (CI): 1.067-2.503, p = 0.024), low PNI (OR: 1.684, 95% CI: 1.108-2.561, p = 0.015), and low HALP (OR: 1.666, 95% CI: 1.097-2.530, p = 0.017) were independently associated with prolonged hospital stay.ConclusionsMalnutrition defined by the CONUT, PNI, and HALP scores was significantly associated with the prolonged hospital stay in liver cancer patients who underwent interventional treatment.